2023
DOI: 10.15671/hjbc.1187546
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Petroleum Removal by Potent Biosurfactant Producer Bacillus Subtilis CC9 Strain Isolated from an Oil Field

Abstract: This study aimed to enhance the removal of petroleum with potent biosurfactant producing bacterial strains (Bacillius subtilis CC9, Enterobacter asburiae WMB1, Klebsiella oxytoca Rizhao 536-1, and Acinetobacter pittii PgBE252) isolated from an oil field. The biosurfactant production was determined by different screening methods such as hemolytic activity, drop-collapse, oil spreading, BATH, emulsification index and surface tension. While the presence of biosurfactant was detected with individual bacterial stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
0
0
Order By: Relevance
“…Recently, it was found through several studies that the use of biological surfactants led to an increased degradation capacity of the degradation of hydrocarbon pollutants [39,40]. It was found that stimulating the production of bio-surfactants by bacterial isolates during the biological treatment of hydrocarbon pollutants led to an increase in the capacity of bacterial isolates to degrade these pollutants due to the increased readiness of these pollutants for the bacterial isolates used in the biological treatment [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found through several studies that the use of biological surfactants led to an increased degradation capacity of the degradation of hydrocarbon pollutants [39,40]. It was found that stimulating the production of bio-surfactants by bacterial isolates during the biological treatment of hydrocarbon pollutants led to an increase in the capacity of bacterial isolates to degrade these pollutants due to the increased readiness of these pollutants for the bacterial isolates used in the biological treatment [40,41].…”
Section: Discussionmentioning
confidence: 99%